2016
DOI: 10.3892/br.2016.742
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor 4 gene rs9960767 polymorphism in bipolar disorder

Abstract: Abstract. The transcription factor 4 (TCF4) gene encodes a helix-loop-helix transcription factor protein, which initiates neuronal differentiation and is primarily expressed during nervous system development. The aim of the present study is to investigate the association of the TCF4 rs9960767 polymorphism and bipolar disorder, which is highly heritable. DNA isolation was performed on 95 patients with bipolar disorder and 108 healthy control subjects to examine the TCF4 rs9960767 polymorphism. Genotypic and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In a study in 2016, Deniz Ozel et al assessed genotype frequencies of the TCF4 gene rs9960767 polymorphism in 95 patients with BD and 108 healthy controls of a Turkish population. Their findings revealed that this variation does not appear to be an independent risk factor for BD; nonetheless, their findings could be biased due to the small size of the studied population [ 77 ]. Few reports have established the link between SCZ and TCF4 rs1261084C/T.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in 2016, Deniz Ozel et al assessed genotype frequencies of the TCF4 gene rs9960767 polymorphism in 95 patients with BD and 108 healthy controls of a Turkish population. Their findings revealed that this variation does not appear to be an independent risk factor for BD; nonetheless, their findings could be biased due to the small size of the studied population [ 77 ]. Few reports have established the link between SCZ and TCF4 rs1261084C/T.…”
Section: Discussionmentioning
confidence: 99%